(untitled) - Weitz, Barton A. (Boston, 2007)
Using real people, real stories, real examples, and real situations, Selling: Building Partnerships, 6/e, delivers an exciting new approach that will help your students develop the partnerships that will promote success in their careers and in their lives. Selling presents selling theories and skills and gives students plenty of opportunity to apply them, showing how salespeople operate in real-life selling situations. This gives students a solid foundation for the more specific sales training they receive on the job
Keywords: Selling,Bán hàng